A traffic accident seen through the eyes of Amazonian shamanism - Guhl Samudio, Juan Felipe (2020)
This work was carried out with the indigenous communities of the Mirití-Paraná river, a short tributary of the Caquetá (Japura) river, located northwest of Colombia’s Amazon basin. I set forth the therapeutic journey of Enio Yukuna, an old man who had a traffic accident and, when telling the story of what happened, recalled that his misfortune began some decades ago when he went tapir hunting in a clay lick. His story and journey are relevant because he talks about how he conceives the land, cosmopolitics, the ontological processes to  learn shamanism, and of the interaction of biomedicine and the Western medical system. In doing so, he speaks explicitly of the typical healing processes that take place in his region, going through shamans of different ethnic groups and varied knowledge that behave in different ways vis-a-vis his afliction. He also talks about gender complementarity with his wife and about prejudice against youth migration, and finally tells how he was sent to Bogota to be treated for his ailment. It is an incredible story that gives us the opportunity to explore the multiple Amazonian universes regarding a person's health.